The impact of health insurance in low- and middle-income countries - Escobar, Maria-Luisa; Griffin, Charles C., 1951-; Shaw, R. Paul (Brookings Institution Press, 2010)
Over the past twenty years, many low- and middle-income countries have experimented with health insurance options. While their plans have varied widely in scale and ambition, their goals are the same: to make health services more affordable through the use of public subsidies while also moving care providers partially or fully into competitive markets. Until now, however, we have known little about the actual effects of these dramatic policy changes. Understanding the impact of health insurance-based care is key to the public policy debate of whether to extend insurance to low-income populatio.